High dose of idarubicin-based regimen for diffuse large cell AIDS-related non-Hodgkin's lymphoma patients: a pilot study - R Gastaldi; P Martino; G Gentile; A Cafolla; I Cordone; G Giannini; C Torromeo; L Palmisano; V Picardi; M Andreotti; G Avvisati; F Mandelli (Haematologica, 2001)
BACKGROUND AND OBJECTIVES: Intensive chemotherapy (CHT) in AIDS-related non-Hodgkin's lymphoma (AIDS-NHL patients) is a vexing problem. Our purpose was to evaluate the feasibility of a high dose idarubicin (HD-IDA)-based regimen in diffuse large cell (DLC) AIDS-NHL patients. DESIGN AND METHODS: Fourteen stage I-IV untreated DLC AIDS-NHL patients with a performance status